2015 IEEE Power &Amp; Energy Society General Meeting 2015
DOI: 10.1109/pesgm.2015.7286504
|View full text |Cite
|
Sign up to set email alerts
|

Financial assessment of battery energy storage systems for frequency regulation service

Abstract: This paper presents a summary of the expected financial performance of battery storage systems providing market-based frequency regulation service for a regional transmission organization. The potential impact of system characteristics and market structure on the profitability of the project is also evaluated. The Discounted Cash Flow analysis was used to determine the benefit-cost ratio, net present value, internal rate of return, and payback period of energy storage projects. The results of this study indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Avendano-Mora and Camm (2015) discussed performance score-based payment for regulation services in PJM and showed AE3% variation can result in a change of AE$3 million in project net present value (NPV) for 50 MW of energy storage capacity. 37 This study also found storage replacement cost as another important assumption that could potentially impact benefit estimation -each additional replacement cost can reduce the NPV by 20%. A summary of the literature covering regulation service benefits is provided in Table 5 below.…”
Section: Regulationmentioning
confidence: 66%
See 1 more Smart Citation
“…Avendano-Mora and Camm (2015) discussed performance score-based payment for regulation services in PJM and showed AE3% variation can result in a change of AE$3 million in project net present value (NPV) for 50 MW of energy storage capacity. 37 This study also found storage replacement cost as another important assumption that could potentially impact benefit estimation -each additional replacement cost can reduce the NPV by 20%. A summary of the literature covering regulation service benefits is provided in Table 5 below.…”
Section: Regulationmentioning
confidence: 66%
“…Sayer et al (2007) analysed the Eastern New York market data and found a $2/MW h reserve price when storage was used for other more valuable applications. 15 Based on an assumption of $30/MW h variable O&M cost and 3000 hours of annual service Table 5 Literature review summary on regulation [10][11][12]14,15,17,[19][20][21][22][23][24][25][29][30][31]37,40,41,46,47 hours, a net benefit of $36/kW-year was estimated. Using CAISO data, Eyer and Corey (2010) estimated a reserve price of $20/kW-year, which is an average of a low-end estimation of $7.9/kW-year with $3/MW h of reserve price while providing services for 30% of the hours in a year and a high-end estimation of $31.5/kW-year with $6/MW h of reserve price and providing services for 60% of the hours in a year.…”
Section: Spinning/non-spinning Reservementioning
confidence: 99%
“…Among the various dynamic analysis methods, the net present value method is widely used because of its simple calculation and intuitive results. The amount of income and expenses during the ESD life cycle are converted into the algebraic sum of the initial values of the project, which can be expressed as [21]:…”
Section: Cost-benefit Analysis Indexesmentioning
confidence: 99%
“…The feasibility and profitability of microgrids participating in the primary frequency control reserve (FCR) market through an aggregator were assessed in [7]. Furthermore, battery energy storage system (BESS) usage on the frequency regulation market was analyzed in [8].According to [9], underground cabling of the network is an effective way for distribution system operators (DSOs) to increase the reliability of power supply. However, underground cabling is expensive.Today, farming is highly automated and electricity-dependent [10], and even short power interruptions are very detrimental.…”
mentioning
confidence: 99%
“…The feasibility and profitability of microgrids participating in the primary frequency control reserve (FCR) market through an aggregator were assessed in [7]. Furthermore, battery energy storage system (BESS) usage on the frequency regulation market was analyzed in [8].…”
mentioning
confidence: 99%